Social Capital Changes in The Phinisi Craftsmen Group at Bulukumba Regency - Musyafir, Ashar; Agustang, Andi; Syukur, Muhammad (Alfuad: Jurnal Sosial Keagamaan, 2023)
Social capital in the relationship pattern of phinisi boat craftsmen is one of the most important capital besides capital in the form of material or goods because it is a bonding agent for relationships. This study aims to determine the forms and factors that cause changes in the social capital of the Pinisi boat craftsmen group in Bulukumba district using a qualitative case study strategy approach. Determination of 3 key informants, namely many categories, moderate categories, few categories. Data were analyzed through data collection, data reduction, data presentation, drawing conclusions and verifying. The results showed that the cooperative pattern of the phinisi boat craftsmen group contained elements of social capital including trust, norms, networks and reciprocal relationships, where the boat entrepreneur fully trusts the retainers, related to the rules that apply in the pattern of working relationships in general have in common, namely the rules cooperation and wages for work in employing groups of craftsmen and in general boat entrepreneurs and retainers help each other when some of them experience difficulties. Social capital in the phinisi boat craftsmen group has changed significantly and gradually in the aspects of investment, technology and management.